2013
DOI: 10.1097/rhu.0b013e3182a6ffc1
|View full text |Cite
|
Sign up to set email alerts
|

Giant Cell Arteritis Causing Symmetric Bilateral Posterior Circulation Infarcts

Abstract: An 82-year-old woman presented with bilateral, symmetric posterior circulation infarctions secondary to giant cell arteritis (GCA). Her atypical clinical presentation included a lack of headache and fever, but she exhibited signs of systemic illness including generalized weakness, cachexia, apathy, and anemia. Laboratory testing revealed a markedly elevated erythrocyte sedimentation rate, but only a borderline elevated C-reactive protein. Head and neck vascular imaging demonstrated a pattern of vertebral arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…With respect to the vasculature pattern, GCA is characterized by subacute granulomatous inflammation of the aorta and its major branches with particular tropism for the extracranial carotid artery branches in patients >50 years of age. 13 The pattern of arterial involvement in 12 autopsy cases demonstrated that the presence of arterial segments showing significant elastic tissue in the media and external elastic lamina was correlated with increased artery involvement. 14 Therefore, the cerebrovascular ischemic events in patients with GCA have been reported to be caused by involvement of extradural vertebral and carotid arteries with high-grade stenosis or occlusions, wherein the elastic fibers are more abundant than those in the intracranial arteries.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the vasculature pattern, GCA is characterized by subacute granulomatous inflammation of the aorta and its major branches with particular tropism for the extracranial carotid artery branches in patients >50 years of age. 13 The pattern of arterial involvement in 12 autopsy cases demonstrated that the presence of arterial segments showing significant elastic tissue in the media and external elastic lamina was correlated with increased artery involvement. 14 Therefore, the cerebrovascular ischemic events in patients with GCA have been reported to be caused by involvement of extradural vertebral and carotid arteries with high-grade stenosis or occlusions, wherein the elastic fibers are more abundant than those in the intracranial arteries.…”
Section: Discussionmentioning
confidence: 99%
“…At GCA onset, CRP is very rarely normal [below ≤ 2.5% ( 81 , 82 )]. It is typically associated with optic signs and rises rapidly within a few days ( 83 ). Combined normal CRP and ESR occurs in <1.2% of cases ( 84 ).…”
Section: Resultsmentioning
confidence: 99%
“…4 In der Literatur wird generell ausgeführt, dass die Riesenzellarteriitis mit Steroiden gut behandelt werden kann. Der hier dargestellte Fall zeigt aber, dass bei diesem Krankheitsbild auch steroidrefraktäre Verläufe möglich sind [3,9].…”
Section: Kasuistikenunclassified